Problem językowy w Ukrainie na tle wojny: stosunek do języka rosyjskiego - Wójcik, Magdalena Ambra (Studia Rossica Posnaniensia, 2025)
As a result of the aggression of the Russian Federation against Ukraine, the language issue once again became topical. A significant part of Ukrainian society began to perceive Russian language as the language of the enemy. A tendency to switch to the Ukrainian language, which is now a factor unifying the nation, became apparent and now its use remains a manifestation of a sense of national identity. Against this background, the question of attitudes towards the Russian language, which is gradually losing its importance, seemed worth analysing. Therefore, the aim of this article was to examine Ukrainian public discourse in terms of statements concerning the language issue, with a particular focus on those relating to the Russian language (Liliya Yaremko and Pavlo Levchuk carried out a similar study but using the survey method). Such a sociolinguistic analysis allowed to present the current situation of this language in Ukraine, thus to indicate how the armed conflict has affected its status in Ukrainian society in terms of everyday communication and school teaching, among others. The research has shown that currently the Russian language is being largely eradicated from the Ukrainian public space, it is being removed from schools, universities. Furthermore, in connection with the growing Ukrainians’ national consciousness, it is being gradually abandoned in everyday life, in the private sphere. Besides, an analogous process is also being observed with regard to Russian culture.